Genetic analysis for pod weight at different developmental stages in Brassica napus L - LI Yun-xia; Variath Murali-Tottekkaad; WU Jian-guo; SHI Chun-hai (浙江大学学报. 农业与生命科学版)
Pod weight (PW), an important quantitative trait very closely related to seed yield, was analyzed using conditional and unconditional genetic models to find out the dynamic effects of genes for this trait during rapeseed development, which comprised of pods harvested at 15, 22, 29, 36 and 43 days after flowering and fertilization. For the unconditional analysis, the additive effects were found to be more important at most stages except for the developmental time of 22 day at which the dominant effects were more prominent. For the conditional analysis, 16 - 22 days after flowering was found to be the most active period for dynamic expression of genes related to pod weight as many new genes were expressed during this period. Heritability analysis revealed that selection in early generations could be effective for improving pod weight in oilseed rape breeding. Prediction of genetic effects for oilseed rape parents showed that Double 20-4, Zhong R-888 and Tower could be used for improving PW in oilseed rape breeding, which Zhong R-888 was the best one. The results further indicate that the heterosis over mid-parent value based on population mean at the stages of 16-22 and 23-29 days was significantly larger than those at other stages.